Elbilsguiden - Modellering av klimatmässig och ekonomisk påverkan vid ett nybilsköp - Lorentzon, Louise; Vranic, Anto; Karlsson, Anna; Faisal, Gulled; Sai, Aron; Alexandersson, Anton (My University, 2017)
The purpose of this project is to produce models for calculating the financial and climatic e↵ects of an investment in a new car. Furthermore, the models are aimed at individuals who are thinking about purchasing an electric vehicle and therefore a secondary purpose is to create an interface through which the models’ results can be communicated. The models have been produced through a thorough study of literature such as scientific reports, and the web pages of di↵erent authorities. The width of the project has required a wide variety of sources of information. The project contains many aspects and the limited time has meant that wide assumptions and simplifications have been made. These are in some cases also caused by confidentiality or the lack of information about a new technology. The result of the project is a set of models and a web site through which these can be accessed by individuals in order to receive recommendations specific to their needs. The models for climatic e↵ects provide the total emissions of carbon dioxide of its equivalents that occur during a car’s production, use and recycling. The models for financial e↵ects provide the monthly cost of the investment during the ownership period. The website then presents the car models which fit the individual best. An analysis of the calculation models shows robustness. The emissions that occur during battery production and the development of the residual value are two factors that clearly need further inquiry. The models are finally visualised through the points of break even between the vehicles and through case studies. The guide to electric vehicles is available at www.elbilsguiden.com.
Keywords: Energi; Transport; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Miljövetenskap; Energy; Transport; Sustainable Development; Innovation & Entrepreneurship; Environmental Sciences